Pyriproxyfen enhances the immunoglobulin G immune response in mice. (15th April 2013) - Sharmin, Tanjina; Satho, Tomomitsu; Irie, Keiichi; Watanabe, Mineo; Hosokawa, Masato; Hiramatsu, Yukihiro; Talukder, Parimal; Okuno, Takahiro; Tsuruda, Shodai; Uyeda, Saori; Fukmits, Yuki; Tamura, Yukie; et al.
ABSTRACT Pyriproxyfen is a juvenile hormone mimic of vital importance for insect development with little risk to humans. This study was performed to investigate whether large doses of pyriproxyfen affect the immune response in mammals. Mice were immunized thrice with ovalbumin in 5% ethanol, with or without pyriproxyfen or alum. Large doses of pyriproxyfen (9 or 15 mM) significantly enhanced specific total IgG immune response. This enhancement was no longer present 24 hr after treatment with pyriproxyfen. These results suggest that pyriproxyfen is a safe chemical. Moreover, pyriproxyfen induced higher titers of IgG2a and enhanced tumor necrosis factor‐alpha and gamma‐interferon responses whereas alum induced IgG1 with enhanced interleukin‐4 and ‐10. These observations indicate that the mechanism of immune enhancement by pyriproxyfen may differ from that of alum.